Contact with Friction Between 3D Beams with Deformable Circular Cross Sections - KAWA, Olga; LITEWKA, Przemyslaw (Engineering Transactions, 2015)
In this paper, contact with friction between three-dimensional elastic beams with deformations at the contact zone is analysed. It is assumed that the analysed beams undergo large displacements, although the strains remain small and the cross sections of the beams are deformed. To include the deformation effect the classical analytical result from Hertzian contact between two elastic cylinders is used [3]. The penalty method is applied to enforce normal contact and friction constraints and the appropriate kinematic variables are defined, linearised and discretised for the finite element method implementation.